Non-isolated Onboard EV Charger Controller Design Based on Port-Hamiltonian Approach - Nattapon Somboonpanya; Surin Khomfoi; Teeraphon Phophongviwat (My University, 2023)
The growth of the electric vehicles (EVs) market and the inadequacy of EV infrastructure, especially EV charging station, have led to an increase in charging EVs at home or the workplace. Onboard EV chargers (OBCs) have been installed on electric vehicles to charge batteries. The trend of increasing power rating and minimized sizing of OBCs, the improvement in stability and performance has been interesting. This paper demonstrates non-isolated EV onboard chargers with controller design based on Port-Hamiltonian control law to approach a robust control system and operate under wide operating range. Finally, the feasibility of the proposed control scheme is validated through experiment in laboratory.
Keywords: Electric Vehicles and Infrastructure; Advanced Battery Technologies Research; Microgrid Control and Optimization